The Cordilleran Ice Sheet: One Hundred and Fifty Years of Exploration and Discovery - Jackson,, Lionel; Clague, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTPresent concepts about the Cordilleran Ice Sheet are the product of observations and ideas of several generations of earth scientists. The limits of glaciation in the Cordillera were established in the last half of the nineteenth century by explorers and naturalists, notably G. M. Dawson, R. G. McConnell, and T. C. Chamberlin. By the turn of the century, the gross configuration of the Cordilleran Ice Sheet had been determined, but the causes of glaciation and ice-sheet dynamics remained poorly understood. This early period of exploration and discovery was followed by a transitional period, from about 1900 to 1950, during which a variety of glacial landforms and deposits were explained (e.g., Channeled Scablands of Washington; "white silts" of southern British Columbia), and conceptual models of the growth and decay of the ice sheet were proposed. Shortly after World War II, there was a dramatic increase in research into all aspects of glaciation in the Canadian Cordillera which has continued unabated to the present. Part of the research effort during this period has been directed at resolving the Cordilleran Ice Sheet in both time and space. Local and regional fluctuations of the ice sheet have been reconstructed through stratigraphie and sedimentological studies, supported by radiocarbon and other dating techniques. Compilations of late Pleistocene ice-flow directions have shown that the Cordilleran Ice Sheet was a mass of coalescent glaciers flowing in a complex fashion from many montane source areas. During the postwar period, research has also begun or advanced significantly in several other disciplines, notably glaciology, process sedimen-tology, geomorphology, paleoecology, and marine geology. Attempts are now being made to quantitatively model the Cordilleran Ice Sheet using computers and the geological database assembled by past generations of earth scientists.